The impact of natives' attitudes towards immigrants on their integration in the host country - Pia Schilling; Steven Stillman (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Exploiting the random allocation of asylum seekers to different locations in Germany, we study the impact of right-wing voting on refugees' integration. We find that in municipalities with more voting for the right-wing AfD, refugees have worse economic and social integration. These impacts are largest for groups targeted by AfD campaigns and refugees are also more likely to suffer from harassment and right-wing attacks in areas with greater AfD support. Positive interactions with locals are also less likely and negative opinions about immigration spillover to supporters of other parties in these areas. On the other hand, stronger support for pro-immigrant parties enhances social integration.
Keywords: J15; J61; Z13; 330; Immigrants' integration; refugees; hostile attitudes; voting behavior